Cross-border Protection of Geographical Indications between China and ASEAN under the Regional Comprehensive Economic Partnership - Siqi, Chen; Mengru, Chen; Rajamanickam, Ramalinggam; manap, nazura binti abdul (Jurnal Cita Hukum, 2026)
Following the entry into force of the RCEP, trade in agricultural products and specialty foods between China and ASEAN has grown, highlighting the role of geographical indications in enhancing quality reputation and market bargaining power. However, cross-border circulation also brings risks such as counterfeiting, free-riding on reputation, and squatting. Existing legal protections struggle to match the risks brought by trade expansion. This paper employs qualitative analysis, comparative analysis, and rule interpretation methodologies. From the perspective of integrating the RCEP framework with China's domestic institutional practices, it proposes advancing procedural alignment and directory-based mutual recognition based on the premise of unified expression through rights information packages. By refining conflict resolution rules and establishing coordinated enforcement mechanisms, it aims to forge an enforceable and sustainable path for regional cooperation.